Rare Holocene sediment deposits from Sodmein Playa (Eastern Desert, Egypt)—Stratigraphic assessment and environmental setting. Issue 2 (12th November 2022) - Henselowsky, Felix; Klasen, Nicole; Timms, Rhys; White, Dustin; Lincoln, Paul; Blockley, Simon; Kindermann, Karin; Bubenzer, Olaf
Abstract: Sodmein Playa is one of the rare Pleistocene open‐air sites in the Eastern Desert of Egypt. Based on the associated stone artefact material, it could be assigned to the Middle Stone Age/Last Interglacial. However, it has not yet been possible to clarify whether the sediments at the basin originated during the Pleistocene or later during Holocene wet phases. Our integrative approach combining Optically Stimulated Luminescence chronology, and cryptotephra analysis, allows us to link the environmental archive of Sodmein Playa with the site of Sodmein Cave. Sodmein Playa indicates wetter climate conditions starting around 9 ka with a (relative) maximum around 7 ka, in line with the general framework of the Holocene Humid Period in Northeast Africa. Despite the climatic similarity, regional environmental differences can still be identified and the effective available water around Sodmein Playa is reduced. The results are well integrated into the current archaeological knowledge with the change from hunter‐gatherers to herders during the Holocene in the area. Analyses of cryptotephra reveal a wide range of source regions, including Eastern and Central Anatolian, the Azores, and the Aegean, as well as those which remain uncorrelated. A tentative correlation with the Holocene cryptotephra record from Sodmein Cave is established.